Detection of Campylobacter jejuni in rectal swab samples from Rousettus amplexicaudatus in the Philippines - HATTA, Yuki; OMATSU, Tsutomu; TSUCHIAKA, Shinobu; KATAYAMA, Yukie; TANIGUCHI, Satoshi; MASANGKAY, Joseph S; PUENTESPINA, Roberto, Jr; ERES, Eduardo; COSICO, Edison; UNE, Yumi; YOSHIKAWA, Yasuhiro; MAEDA, Ken; et al. (Journal of Veterinary Medical Science, 2016)
Bats are the second diversity species of mammals and widely distributed in the world. They are thought to be reservoir and vectors of zoonotic pathogens. However, there is scarce report of the evidence of pathogenic bacteria kept in bats. The precise knowledge of the pathogenic bacteria in bat microbiota is important for zoonosis control. Thus, metagenomic analysis targeting the V3-V4 region of the 16S rRNA of the rectal microbiota in Rousettus amplexicaudatus was performed using high throughput sequencing. The results revealed that 103 genera of bacteria including Camplyobacter were detected. Campylobacter was second predominant genus, and Campylobacter coli and Campylobacter jejuni were identified in microbiome of R. amplexicaudatus. Campylobacteriosis is one of the serious bacterial diarrhea in human, and the most often implicated species as the causative agent of campylobacteriosis is C. jejuni. Therefore, we investigated the prevalence of C. jejuni in 91 wild bats with PCR. As a result of PCR assay targeted on 16S-23S intergenic spacer, partial genome of C. jejuni was detected only in five R. amplexicaudatus. This is the first report that C. jejuni was detected in bat rectal swab samples. C. jejuni is the most common cause of campylobacteriosis in humans, transmitted through water and contact with livestock animals. This result indicated that R. amplexicaudatus may be a carrier of C. jejuni.